2006
DOI: 10.1149/1.2141656
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Characterization of 5-Aminotetrazole as a Corrosion Inhibitor in Copper Chemical Mechanical Polishing [J. Electrochem. Soc., 152, C827 (2005)]

Abstract: On page C831, Fig. 10 should have appeared as below. Figure 10. Inline SEM images ͑a͒ BTA and ͑b͒ ATRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…39 In this study, 3-amino-1,2,4-triazole, which has a similar structure to other Cu corrosion inhibitors such as benzotriazole or 5-aminotetrazole, was added to the electrolyte in order to suppress further growth. 40 The addition of 3-amino-1,2,4-triazole strongly enhanced nucleation density and considerably improved the coverage of 0.1 s into deposition compared to cases without suppressor ͑Fig. 12͒.…”
Section: D392mentioning
confidence: 99%
“…39 In this study, 3-amino-1,2,4-triazole, which has a similar structure to other Cu corrosion inhibitors such as benzotriazole or 5-aminotetrazole, was added to the electrolyte in order to suppress further growth. 40 The addition of 3-amino-1,2,4-triazole strongly enhanced nucleation density and considerably improved the coverage of 0.1 s into deposition compared to cases without suppressor ͑Fig. 12͒.…”
Section: D392mentioning
confidence: 99%
“…To inhibit Cu corrosion, benzotriazole ͑BTA͒ or 5-aminotetrazole ͑ATRA͒ is commonly used. [9][10][11] An organic additive of the carboxylic group was added as a complexing agent to improve the removal rate of Cu. At present, citric acid, [12][13][14] oxalic acid, 15 and glycine [16][17][18] were introduced as the complexing agent and their properties and performance investigated.…”
mentioning
confidence: 99%
“…Previously, our group showed that ATRA was an effective corrosion inhibitor for use in Cu CMP slurries. 24 On the basis of that result, ATRA was selected as a candidate corrosion inhibitor in this study and the effects of the addition of ATRA on the polishing rate and static etch rate were investigated. Figure 11a shows the results of Cu polish rate and static etch rate with changing ATRA concentration and Fig.…”
Section: H956mentioning
confidence: 99%